2021
DOI: 10.1186/s13722-021-00249-3
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of medications for opioid use disorder among youth engaged in primary care: data from 6 health systems

Abstract: Purpose Little is known about prevalence and treatment of OUD among youth engaged in primary care (PC). Medications are the recommended treatment of opioid use disorder (OUD) for adolescents and young adults (youth). This study describes the prevalence of OUD, the prevalence of medication treatment for OUD, and patient characteristics associated with OUD treatment among youth engaged in PC. Methods This cross-sectional study includes youth aged 16–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
(34 reference statements)
3
2
0
Order By: Relevance
“…Particularly, older young adults aged 22–25 were more likely to seek treatment compared to those aged 18–21. These findings largely converge with previous studies ( Bagley et al., 2021 ; Liebling et al., 2016 ; Windle et al., 1991 ; Wu et al., 2011 ). For example, the Primary Care Opioid Use Disorders (PROUD) trial revealed that less than one in six youth aged 16–17 received buprenorphine or naltrexone for opioid use disorders while about a third of young adults aged 18–25 years received medications for opioid use disorders ( Bagley et al., 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Particularly, older young adults aged 22–25 were more likely to seek treatment compared to those aged 18–21. These findings largely converge with previous studies ( Bagley et al., 2021 ; Liebling et al., 2016 ; Windle et al., 1991 ; Wu et al., 2011 ). For example, the Primary Care Opioid Use Disorders (PROUD) trial revealed that less than one in six youth aged 16–17 received buprenorphine or naltrexone for opioid use disorders while about a third of young adults aged 18–25 years received medications for opioid use disorders ( Bagley et al., 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…These findings largely converge with previous studies ( Bagley et al., 2021 ; Liebling et al., 2016 ; Windle et al., 1991 ; Wu et al., 2011 ). For example, the Primary Care Opioid Use Disorders (PROUD) trial revealed that less than one in six youth aged 16–17 received buprenorphine or naltrexone for opioid use disorders while about a third of young adults aged 18–25 years received medications for opioid use disorders ( Bagley et al., 2021 ). Our findings underscore the pressing need for the treatment of SUDs, especially among younger young adults.…”
Section: Discussionsupporting
confidence: 92%
“…Careful assessment of youths' goals and preferences as part of treatment planning may also reveal additional substance use, health, and psychosocial service needs. As shown by our study and others (Bagley et al, 2021;Krebs et al, 2021;Lim et al, 2021), youth with OUD were engaging in poly-substance use and have concurrent mental health conditions, which are crucial to address as they can increase risk of overdose (Moe et al, 2021) and impact OAT initiation and continuity (Lind et al, 2019). In this novel integrated youth-specific OAT program, youth had access to interdisciplinary services (e.g., primary care, psychiatry, counselling) as needed, and our chart review suggests that a high proportion of youth engaged in these optional supports.…”
Section: Discussionsupporting
confidence: 88%
“…However, the majority of participants in these existing studies were over the age of 30, and studies have not focused on the impact of RMG and safer supply prescribing on YPWUD, including those who have received an OUD diagnosis. Improving access to a continuum of care for these populations – ranging from comprehensive harm reduction services to abstinence-orientated treatment and recovery programming – has been identified as an urgent public health priority globally ( Bagley et al 2021 ; Canêdo et al, 2022 ; Hadland et al, 2018 ; Ingoglia, 2020 ; Winhusen et al, 2020 ). We undertook this qualitative study to examine how RMG prescriptions of hydromorphone tablets specifically shaped YPWUD's substance use and care trajectories.…”
Section: Introductionmentioning
confidence: 99%